A Multi-Radio Unification Protocol for IEEE 802.11 Wireless Networks - Adya, Atul; Bahl, Victor; Padhye, Jitu; Wolman, Alec; Zhou, Lidong (IEEE Computer Society 2004, 2004)
We present a link layer protocol called the Multi-radio Unification Protocol or MUP. On a single node, MUP coordinates the operation of multiple wireless network cards tuned to non-overlapping frequency channels. The goal of MUP is to optimize local spectrum usage via intelligent channel selection in a multihop wireless network. MUP works with standard-compliant IEEE 802.11 hardware, does not require changes to applications or higher-level protocols, and can be deployed incrementally. The primary usage scenario for MUP is a multihop community wireless mesh network, where cost of the radios and battery consumption are not limiting factors. We describe the design and implementation of MUP, and analyze its performance using both simulations and measurements based on our implementation. Our results show that under dynamic traffic patterns with realistic topologies, MUP significantly improves both TCP throughput and user perceived latency for realistic workloads.
1st International Conference on Broadband Networks (BROADNETS 2004)